Successional Change of the Fungal Microbiome Pine Seedling Roots Inoculated With Tricholoma matsutake - Park, Ki Hyeong; Oh, Seung-Yoon; Yoo, Shinnam; Park, Myung Soo; Fong, Jonathan J.; Lim, Young Woon (Frontiers in Microbiology, 2020)
The pine mushroom (Tricholoma matsutake; Agaricales, Tricholomataceae) is an ectomycorrhizal fungus that produces a commercially valuable, edible mushrooms. Attempts to artificially cultivate T. matsutake has so far been unsuccessful. One method used to induce T. matsutake to produce fruiting bodies of in the wild is shiro (mycelial aggregations of T. matsutake) transplantation. In vitro ectomycorrhization of T. matsutake with seedlings of Pinus densiflora has been successful, but field trials showed limited production of fruiting bodies. Few studies have been done to test what happens after transplantation in the wild, whether T. matsutake persists on the pine seedling roots or gets replaced by other fungi. Here, we investigated the composition and the interaction of the root fungal microbiome of P. densiflora seedlings inoculated with T. matsutake over a 3 year period after field transplantation, using high-throughput sequencing. We found a decline of T. matsutake colonization on pine roots and succession of mycorrhizal fungi as P. densiflora seedlings grew. Early on, roots were colonized by fast-growing, saprotrophic Ascomycota, then later replaced by early stage ectomycorrhiza such as Wilcoxina. At the end, more competitive Suillus species dominated the host roots. Most of the major OTUs had negative or neutral correlation with T. matsutake, but several saprotrophic/plant pathogenic/mycoparasitic species in genera Fusarium, Oidiodendron, and Trichoderma had positive correlation with T. matsutake. Four keystone species were identified during succession; two species (Fusarium oxysporum, and F. trincintum) had a positive correlation with T. matsutake, while the other two had a negative correlation (Suillus granulatus, Cylindrocarpon pauciseptatum). These findings have important implications for further studies on the artificial cultivation of T. matsutake.